2016
DOI: 10.1016/j.janxdis.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Psychological perspectives on fear of childbirth

Abstract: The objective of this narrative review was to examine the literature on fear of childbirth from a psychological perspective, addressing the specificity of childbirth fear, the pathways of fear acquisition, and the physiological, cognitive and behavioral aspects of fear. Systematic procedures for literature search, inclusion and exclusion left 86 original research papers for analysis. Findings summarize the body of knowledge for each area of interest, as well as the number of studies addressing each theme. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(131 citation statements)
references
References 116 publications
5
115
1
10
Order By: Relevance
“…Fear of childbirth (FOC) exists on a continuum from normal worries and fears, to severe fear, (tocophobia) . Although tocophobia is not clearly defined, the adverse impact of FOC on women's health and well‐being in the perinatal period is well‐established .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of childbirth (FOC) exists on a continuum from normal worries and fears, to severe fear, (tocophobia) . Although tocophobia is not clearly defined, the adverse impact of FOC on women's health and well‐being in the perinatal period is well‐established .…”
Section: Introductionmentioning
confidence: 99%
“…Fear of childbirth (FOC) exists on a continuum from normal worries and fears, to severe fear, (tocophobia) . Although tocophobia is not clearly defined, the adverse impact of FOC on women's health and well‐being in the perinatal period is well‐established . Previous studies have reported that sleep disturbances, nightmares, palpitations, stomach pains, panic attacks, flashbacks (after trauma) and a request for a cesarean are associated with FOC .…”
Section: Introductionmentioning
confidence: 99%
“…The most severe fears can resemble a phobia of childbirth, termed “tokophobia” (Hofberg & Brockington, ; Zar, Wijma, & Wijma, ). No clear definition or identification of key mechanisms contributing to the development of FOC exists (Klabbers, van Bakel, van den Heuvel, & Vingerhoets, ; Rondung, Thomtén, & Sundin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of the role of causal mechanisms like these is of key value for the development of effective interventions. With respect to childbirth‐related fear or anxiety, very few studies in the field have tried to identify mechanisms in this sense, and both cognitive and behavioral mechanisms contributing to the etiology and maintenance of this form of anxiety are still largely unexplored …”
Section: Introductionmentioning
confidence: 99%